EDGELESS FLAT PLOWING STEP PLUG WITH DISK ANGLE CUTTER - D.N. Choriyeva (Journal of Artificial Intelligence and Digital Economy, 2024)
The article presents information about the construction scheme of the step-shaped plow with a disk-shaped angle cutter, designed to prepare the soil for plowing without an edge in one pass, and the technological process it performs.